“Criminalization” of human rights?: Swings and paradoxes on the jurisprudence of Inter-American Court of Human Rights - Saucier Calderón, Jean-Paul (2016)
The evolving relationship between international human rights law and criminal law is marked by a passage from a role of moderation to one of legitimization. While international human rights law was previously critical of criminal law as an instrument of state repression, the last few decades witnessed a shift towards a victim-centred conception of criminal law as a means to protect and enforce certain human rights. This contrasts with a liberal conception of human rights as a check on the power of the state through the use of its criminal law authority. This development manifests itself through what may be dubbed the "criminalization” of Inter-American human rights law. This contribution explores this phenomenon of “criminalization” and its various illustrations, particularly through the Inter-American Court of Human Rights’ discourse with respect to amnesty laws and prescription.